Battery pack

By using spacers with appropriate elastic modulus and controlling the orientation of graphite particles in the secondary battery pack, the problem of negative electrode deflection caused by graphite particle expansion was solved, thereby improving the cycle performance and capacity retention of the battery pack.

CN121484340APending Publication Date: 2026-02-06PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511074361.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-05
Filing Date
2025-08-01
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

In a secondary battery pack with graphite particles oriented vertically along the current collector foil, the graphite particles expand significantly in the horizontal direction of the negative electrode current collector foil, causing the negative electrode to flex and affecting battery performance.

Method used

By using spacers with an elastic modulus of 0.3 MPa or higher and 5 MPa or lower between multiple square secondary cells arranged in a specified direction, the reaction of graphite particles in the negative electrode active material layer is suppressed, and the expansion of the electrode body is reduced by controlling the orientation and aspect ratio of the graphite particles.

Benefits of technology

It effectively suppressed the bending of the negative electrode, improved the cycle characteristics and cycle capacity retention of the battery pack, and reduced the expansion of the electrode body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121484340A_ABST
    Figure CN121484340A_ABST
Patent Text Reader

Abstract

Provided is an electricity storage device with improved cycle capacity retention rate. The battery pack includes a plurality of rectangular secondary batteries. The plurality of rectangular secondary batteries are stacked with a spacer therebetween. The spacer includes an elastic layer having an elastic modulus of 0.3 MPa or more and 5 MPa or less. The prismatic secondary battery includes: an electrode body including a negative electrode having a negative electrode collector foil and a negative electrode active material layer formed on the negative electrode collector foil and including graphite particles, and a positive electrode; a non-aqueous electrolyte solution containing a carbonate ester; and a case that accommodates the electrode body and the non-aqueous electrolyte solution. The degree of orientation of the graphite particles contained in the negative electrode active material layer is 180 or less. Furthermore, in an electron microscope image obtained by capturing an osmium-dyed negative electrode after charging and discharging the rectangular secondary battery, 300 or more graphite particles are randomly extracted, and the value obtained by dividing the number (A) of graphite particles, the inside of which is dyed, by the total number (B) of graphite particles among these graphite particles is less than 0.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to battery packs. Background Technology

[0002] Lithium-ion batteries, nickel-metal hydride batteries, and other rechargeable batteries are suitable for use as high-output power sources in portable devices such as personal computers and mobile terminals, as well as in vehicles such as battery electric vehicles (BEVs) due to their lightweight nature and high energy density. In applications requiring such high-output power, battery packs comprising multiple rechargeable cells (single cells) are used.

[0003] Orienting graphite particles is known as a means of improving the performance of secondary batteries. For example, it is known that by orienting graphite particles, the cycle characteristics of the battery, the rate of charge carrier absorption and release, etc., are improved. In Japanese Patent Application Publication No. 2003-197189, a method for manufacturing a negative electrode for a secondary battery with high discharge capacity and excellent cycle characteristics during high charge and discharge is disclosed by solidifying the graphite particles in a state in which the (002) surfaces between the graphite particles are oriented in the same direction in a magnetic field.

[0004] In addition, Japanese Patent Application Publication No. 2016-184534 discloses that by orienting graphite particles, it is possible to suppress the expansion of graphite particles in the direction perpendicular to the current collector foil (the thickness direction of the electrode body) during the absorption of charge carriers.

[0005] In battery packs, spacers are sometimes arranged between adjacent secondary batteries, as described in Japanese Patent Application Publication No. 2018-181765. In Japanese Patent Application Publication No. 2018-181765, a load is applied to the orientation of the secondary batteries and the spacers. Furthermore, it discloses that by using spacers, even when the positive and negative electrodes expand and contract during charging and discharging, dimensional changes in the electrode bodies can be suppressed.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-197189

[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-184534

[0010] Patent Document 3: Japanese Patent Application Publication No. 2018-181765

[0011] Patent Document 4: Japanese Patent Application Publication No. 2015-138644 Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] However, in a secondary battery pack where graphite particles are oriented perpendicular to the current collector foil, the graphite particles expand significantly in the horizontal direction of the negative electrode current collector foil. As a result, deflection occurs at the negative electrode, leading to a decrease in battery performance. Therefore, it was found that there is room for improvement in suppressing negative electrode deflection in such battery packs.

[0014] This disclosure was made in view of this actual situation, and its main purpose is to provide a battery pack that suppresses the occurrence of negative electrode flexure and improves cycle characteristics.

[0015] Methods for solving problems

[0016] The battery pack disclosed herein comprises a plurality of square secondary cells arranged in a predetermined direction, and spacers disposed between the arranged square secondary cells. The spacers comprise an elastic layer with an elastic modulus of 0.3 MPa or more and 5 MPa or less. The square secondary cell comprises: an electrode body comprising a negative electrode having a negative current-collecting foil and a negative active material layer formed on the negative current-collecting foil, and a positive electrode having a positive current-collecting foil and a positive active material layer formed on the positive current-collecting foil; a non-aqueous electrolyte comprising carbonate; and a shell housing the electrode body and the non-aqueous electrolyte. The negative active material layer comprises graphite particles as the negative active material. The orientation degree of the graphite particles is 180 degrees or less. Furthermore, regarding the graphite particles, a charge cycle of 30% to 80% and a discharge cycle of 80% to 30% is considered as one cycle. After at least one such charge-discharge cycle, the square secondary battery is removed, and more than 300 graphite particles are randomly selected from the electron microscope image of the osmium-stained negative electrode. The value obtained by dividing the number of stained graphite particles (A) inside these particles by the total number of graphite particles (B) is less than 0.5.

[0017] According to this battery pack, the reaction between graphite particles and electrolyte is difficult to occur within the graphite particles contained in the negative electrode active material layer. Therefore, the formation and accumulation of by-reaction products do not occur within the graphite particles, thus reducing the expansion of the electrode body associated with battery charging and discharging. In this respect, for the oriented negative electrode, the horizontal expansion of the negative electrode current collector foil is also suppressed, thus preventing the bending of the negative electrode.

[0018] The graphite particles in the negative electrode active material layer of the battery pack disclosed herein have an aspect ratio of 1.2 or higher. This allows for a more reliable reduction in the orientation of the graphite particles. This effect further improves the cycle capacity retention rate of the battery pack. Attached Figure Description

[0019] Figure 1A perspective view is shown to schematically illustrate the structure of a battery pack according to one embodiment disclosed herein.

[0020] Figure 2 A longitudinal cross-sectional view of a battery pack according to one embodiment disclosed herein is shown schematically.

[0021] Figure 3 A perspective view is shown schematically illustrating the structure of a secondary battery according to one embodiment disclosed herein.

[0022] Figure 4 A longitudinal cross-sectional view of a secondary battery according to one embodiment disclosed herein is shown schematically.

[0023] Figure 5 An exploded view is shown schematically illustrating the configuration of a wound electrode body according to one embodiment disclosed herein.

[0024] Figure 6 The figure is shown schematically as an electron microscope image obtained after osmium staining of the negative electrode according to one embodiment disclosed herein.

[0025] Figure 7 This diagram illustrates how side reactions can easily occur inside graphite particles.

[0026] Figure 8 This is an illustrative diagram used to explain the expansion of oriented graphite particles.

[0027] Figure 9 This is an explanatory diagram used to illustrate the bending state of the negative electrode. Detailed Implementation

[0028] <Definitions of Terms>

[0029] The following describes in detail a typical embodiment of the battery pack of this disclosure, with reference to the accompanying drawings. Matters not specifically mentioned in this specification, i.e., matters necessary for implementation (e.g., the general structure and manufacturing process of the battery, which are not features of this disclosure), can be grasped by those skilled in the art based on prior art. This disclosure can be implemented based on the content disclosed in this specification and common technical knowledge in the field. It should be noted that in the following drawings, the same reference numerals are used for components and parts that perform the same function, and sometimes repeated descriptions are omitted or simplified. Furthermore, the dimensional relationships (length, width, thickness, etc.) in the drawings do not reflect actual dimensional relationships.

[0030] In this specification, the term "secondary battery" refers to any battery capable of repeated charging and discharging by the movement of charge carriers between the positive and negative electrodes. Examples of secondary batteries include lithium-ion secondary batteries, nickel-metal hydride batteries, and nickel-cadmium batteries. Furthermore, in this specification, the term "battery pack" refers to a collection of batteries in which multiple secondary batteries are arranged and electrically connected. It should be noted that the following description uses a typical secondary battery, namely a lithium-ion secondary battery 1, and a battery pack 100 using the lithium-ion secondary battery 1 as examples to illustrate this embodiment. In this specification, the term "lithium-ion secondary battery" refers to a secondary battery that utilizes lithium ions as charge carriers and achieves charging and discharging through the movement of charges accompanying lithium ions between the positive and negative electrodes.

[0031] In this specification, when the numerical range is recorded as "A~B (where A and B are arbitrary values)," it means "above A and below B," and includes the meanings of "greater than A and less than B," "greater than A and less than B," and "above A and less than B."

[0032] <Battery Pack>

[0033] The battery pack 100 disclosed herein includes a plurality of square secondary batteries (here, lithium-ion secondary batteries 1). Furthermore, in the battery pack of this disclosure, the plurality of lithium-ion secondary batteries 1 and a plurality of spacers 120 are arranged in a predetermined direction. Figure 1 A perspective view is shown to schematically illustrate the structure of a battery pack according to one embodiment disclosed herein. Figure 1 In the accompanying drawings, the front side in the specified direction (column direction Z) is designated as "front" (reference numeral F), and the depth side is designated as "rear" (reference numeral Rr). It should be noted that in the following description, reference numerals L, R, U, and D in the drawings represent the left, right, top, and bottom of the battery pack 100 and the lithium-ion secondary battery 1 described later. Furthermore, the directions are defined as vertical (height direction Y) and horizontal (width direction X). However, these are merely directions for ease of explanation and do not impose any limitations on the arrangement of the battery pack 100.

[0034] Figure 2 A longitudinal cross-sectional view of a battery pack according to one embodiment disclosed herein is shown schematically. Figure 2 For along Figure 1 The longitudinal section view of line II-II. (See figure) Figure 2As shown, in the battery pack 100, multiple lithium-ion secondary batteries 1 are stacked in a predetermined direction (here, the column direction Z) via spacers 120. In this embodiment, adjacent lithium-ion secondary batteries 1 are arranged such that the long side 11b1 of one lithium-ion secondary battery 1 is alternately opposite to the long side 11b2 of another lithium-ion secondary battery 1. That is, the orientation of the lithium-ion secondary batteries 1 is alternately changed by arranging the positive electrode external terminals 14 and negative electrode external terminals 15 alternately. The positive electrode external terminal 14 of one adjacent lithium-ion secondary battery 1 and the negative electrode external terminal 15 of another lithium-ion secondary battery 1 are electrically connected to each other by a metal busbar (not shown). However, the arrangement and connection of the lithium-ion secondary batteries 1 are not limited. The lithium-ion secondary batteries 1 can be connected in series or in parallel.

[0035] <Constraint Components>

[0036] Battery pack 100 Figure 1 and Figure 2 As shown, a constraint member 110 is provided to constrain a plurality of lithium-ion secondary batteries 1 and a plurality of spacers 120 in the column direction Z. The constraint member 110 is configured to apply a predetermined load to the plurality of lithium-ion secondary batteries 1 and the plurality of spacers 120 along the column direction Z. It should be noted that the constraint load is not particularly limited as long as it does not significantly impair the technical effect of this disclosure. The initial constraint load is approximately 0.1 MPa to 1 MPa (preferably approximately 0.2 MPa to 0.7 MPa). In this embodiment, the constraint member 110 is as follows... Figure 1 As shown, it is composed of a pair of end plates 112a and 112b, a pair of side plates 113a and 113b, and a bottom plate 111. Multiple lithium-ion secondary batteries 1 and multiple spacers 120 are housed inside the constraint member 110. The constraint member 110 can be a module housing. However, this embodiment does not limit the shape of the constraint member 110 to a box shape. For example, the pair of side plates 113a and 113b can be fastened together. The constraint member 110 can also be a frame.

[0037] End plates 112a and 112b are respectively positioned at the start and end points in the column direction Z. Wherein, as... Figure 1As shown, end plate 112a is positioned at the front F of the battery pack 100. End plate 112b is positioned at the rear Rr of the battery pack. Regarding the side plates 113a and 113b, since the lithium-ion secondary batteries 1 are arranged along the column direction Z, the short sides 11c1 and 11c2 support the lithium-ion secondary batteries 1. In the constraint member 110, a pair of end plates 112a and 112b are connected by a pair of side plates 113a and 113b and a plurality of screws 114. However, the end plates 112a and 112b can be connected to the side plates 113a and 113b using adhesives or welding. In this embodiment, a plurality of lithium-ion secondary batteries 1 and a plurality of spacers 120 are alternately arranged between the pair of end plates 112a and 112b. Furthermore, between the pair of side plates 113a and 113b, a plurality of lithium-ion secondary batteries 1 and a plurality of spacers 120 are fixed along the column direction Z. Therefore, a constraint load is applied from the column direction Z to hold the battery pack 100 together for the plurality of lithium-ion secondary batteries 1 and the plurality of spacers 120. In addition, the base plate 111 is configured to abut against the bottom wall 11a of the plurality of lithium-ion secondary batteries 1.

[0038] The materials for the end plates 112a, 112b, side plates 113a, 113b, and bottom plate 111 are not particularly limited. These materials can be selected from metals or resins, etc. Furthermore, the materials of each component can be the same or different. From the viewpoint of the strength of the constraint member 110 and the application of appropriate loads to the lithium-ion secondary battery 1 and the spacer 120, these materials are preferably metals. Furthermore, the shapes of the end plates 112a, 112b, side plates 113a, 113b, and bottom plate 111 are not particularly limited. In this embodiment, the end plates 112a, 112b, and bottom plate 111 are rectangular and have a predetermined thickness (e.g., a thickness sufficient to drive in multiple screws 114). Additionally, the side plates 113a, 113b are formed thinner than the end plates 112a, 112b, and bottom plate 111. At both ends of a pair of side plates 113a, 113b, as... Figure 1 As shown, protruding ribs 113c are arranged approximately vertically in a relatively opposite manner. These ribs 113c press against the edge of the sealing plate 12 of the plurality of lithium-ion secondary batteries 1 housed in the restraining member 110. This retains the plurality of lithium-ion secondary batteries 1 inside the restraining member 110.

[0039] <spacers>

[0040] Spacers 120 are disposed between the opposing long sides 11b1 and 11b2 of adjacent lithium-ion secondary batteries 1. Spacers 120 act as a buffer material to protect the lithium-ion secondary batteries 1 from external impacts, vibrations, etc., affecting the battery pack 100. Additionally, spacers 120 apply a certain load to the lithium-ion secondary batteries 1 to suppress the expansion of the casing 10. Spacers 120 are also referred to as inter-cell separators.

[0041] The elastic modulus of the elastic layer of the spacer 120 disclosed herein is 0.3 MPa or more and 5 MPa or less. It should be noted that in this embodiment, the spacer 120 is entirely composed of an elastic layer, and the "elastic modulus of the elastic layer of the spacer" is also referred to below as the elastic modulus of the spacer. The smaller the elastic modulus of the spacer 120, the softer the spacer 120 is, and the easier it is to elastically deform. Therefore, if a spacer 120 with a small elastic modulus is used, it is easier to absorb the swelling of the shell 10. On the other hand, if the elastic modulus is high, it is easier to suppress the swelling of the shell 10. From this viewpoint, the lower limit of the elastic modulus of the spacer 120 is preferably 0.3 MPa or more, more preferably 0.4 MPa or more, and even more preferably 0.5 MPa or more. Furthermore, the upper limit of the elastic modulus of the spacer 120 is preferably 5 MPa or less, more preferably 4 MPa or less, and even more preferably 3 MPa or less. It should be noted that in this specification, the term "elastic modulus" refers to the value calculated as described below. Prepare a square test piece measuring 5cm x 5cm and measure its initial thickness (mm) using a micrometer. Next, using a conventional compression testing apparatus, compress the test piece at a constant speed in the thickness direction (X) at a compression rate of 30 N / min (12 kPa / min) until the compressive load per unit area of ​​the test piece reaches 3.9 MPa. Measure the compressive load (MPa) and the thickness after compression (mm). Then, based on the compressive load (MPa) and the thickness after compression (mm), plot the compression ratio (%) calculated as (initial thickness - compressed thickness (mm)) / initial thickness (mm) × 100 on the horizontal axis, and plot the compressive load (N / mm) on the horizontal axis. 2 =MPa) is shown on the compression load-compression ratio curve (FS curve) on the vertical axis. The slope of the approximate straight line A in the range of 1% to 20% of the compression ratio of the FS curve (horizontal axis: compression ratio, vertical axis: compression load) is set as the elastic modulus (MPa).

[0042] The shape and size of the spacer 120 are not particularly limited as long as they do not significantly impair the technical effects of this disclosure. However, regarding the spacer 120, by setting a predetermined thickness, it can elastically deform as the lithium-ion secondary battery 1 expands, thus easily absorbing the expansion. From the viewpoint of easily absorbing the expansion of the lithium-ion secondary battery 1, the lower limit of the thickness of the spacer 120 is preferably 5% or more of the thickness of the lithium-ion secondary battery 1 (length in the column direction Z), more preferably 7.5% or more, and even more preferably 10% or more. In addition, from the viewpoint of improving the energy density of the battery pack 100, the upper limit of the thickness of the spacer 120 is preferably 40% or less of the thickness of the lithium-ion secondary battery 1, more preferably 35% or less, and even more preferably 30% or less. It should be noted that, here, the thickness of the spacer 120 refers to the thickness constrained up to the battery pack 100.

[0043] The material of the spacer 120 is not particularly limited as long as it does not significantly impair the technical effects of this disclosure. Considering the aforementioned range of elastic modulus, it is preferable to use a polymeric material. Examples of polymeric materials include fluoropolymers, polyester resins, polyolefin resins, silicone resins, acrylic resins, chloroprene resins, polysulfone (PSF), polystyrene (PS), polyimide, and polyamide resins. Furthermore, rubber-based materials (thermosetting elastomers) are preferred as the material of the spacer 120. Examples of rubber-based materials include natural rubber (NR), isoprene rubber (IR), styrene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), butyl rubber (I IR), nitrile rubber (NBR), ethylene propylene rubber (EPDM), acrylic rubber (ACM), polyurethane rubber, silicone rubber, epichlorohydrin rubber (ECO), and norbornene rubber.

[0044] Furthermore, the spacer 120 may have an elastic portion having the elastic modulus described above, and a heat-insulating layer portion that blocks heat conduction from the contacting lithium-ion secondary battery 1. The material of the heat-insulating layer portion is formed by mixing and molding an inorganic filler (e.g., alumina) and a binder. Since the heat-insulating layer portion contains an air layer, its thermal conductivity can be reduced. As a result, heat-induced degradation of the spacer 120 can be suppressed. In addition, even if the lithium-ion secondary battery 1 heats up, other lithium-ion secondary batteries 1 are less likely to be affected. Therefore, thermal runaway of the battery pack can be suppressed. The thickness of the heat-insulating layer portion is preferably 2.5% or more of the thickness of the lithium-ion secondary battery 1 (length in the Z-direction), more preferably 5% or more. The spacer 120 may be a two-layer structure consisting of an elastic portion and a heat-insulating layer portion. However, it is not limited to providing a heat-insulating layer portion; by mixing inorganic fillers or the like into the elastic portion, the spacer 120 can be given additional heat-insulating functionality.

[0045] It should be noted that the battery pack 100 can be used for various applications. However, in particular, swelling is prone to occur in secondary batteries with square casings during charge-discharge cycles, so it is suitable for applications requiring high capacity (e.g., a secondary battery energy density of 500 Wh / L or higher). Examples of such applications include power sources (drive power supplies) for motors installed in vehicles such as cars and trucks. Furthermore, there are no particular limitations on the type of vehicle; examples include plug-in hybrid electric vehicles (PHEVs), hybrid electric vehicles (HEVs), and battery electric vehicles (BEVs).

[0046] Secondary batteries

[0047] Figure 3 A perspective view is shown schematically illustrating the structure of a secondary battery according to one embodiment disclosed herein. Figure 4 A longitudinal cross-sectional view of a secondary battery according to one embodiment disclosed herein is shown schematically. Figure 4 For along Figure 3 A schematic longitudinal cross-sectional view of the secondary cell along the IV-IV line. Additionally, in Figure 4 In this image, a portion of the wound electrode body 20 is shown in perspective to reveal the structure of the wound electrode body 20.

[0048] <Shell>

[0049] like Figure 3 As shown, in the lithium-ion secondary battery 1 according to this embodiment, the casing 10 is rectangular in shape, specifically a flat square. The casing 10 includes a main body 11 that houses the electrode body and electrolyte (not shown), and a sealing plate 12 (cover) that seals the opening of the main body 11. The main body 11 and the sealing plate 12 are sealed by welding, such as laser welding. The material of the casing 10 is not particularly limited, as long as it is the same as the material conventionally used in such secondary batteries. For example, the casing 10 is made of a lightweight, thermally conductive metal such as aluminum. However, the configuration of the casing 10 can be changed. For example, a flexible laminated film can be used as the casing.

[0050] In this embodiment, the main body 11 of the housing 10 is composed of a rectangular and elongated bottom wall 11a, a pair of long side surfaces 11b1 and 11b2 extending from the bottom wall 11a and facing each other, and a pair of short side surfaces 11c1 and 11c2. Additionally, the housing 10 is provided with a safety valve 13 and an injection port (not shown). The safety valve 13 is a thin-walled valve designed to open when the internal pressure of the housing 10 rises above a predetermined level. The injection port is a hole for injecting electrolyte. Since the injection port is no longer needed after the electrolyte is injected, it can be sealed using methods such as laser welding. Alternatively, the injection port can also be sealed by installing a plug.

[0051] The positive external terminal 14 and negative external terminal 15 for external connection are provided exposed outside the housing 10. These external terminals are electrically connected to the wound electrode body 20 housed within the housing 10 via the positive internal terminal 16 or the negative internal terminal 17. The positive external terminal 14 and negative external terminal 15 are made of metal. For example, aluminum or an aluminum-based alloy can be used as the positive external terminal 14. For example, copper or a copper alloy can be used as the negative external terminal 15.

[0052] The positive electrode internal terminal 16 and the negative electrode internal terminal 17 are made of metal. For the positive electrode internal terminal 16, from the viewpoint of improving the bonding strength with the positive electrode plate 31c (or the non-forming portion 31a of the positive electrode active material layer), aluminum or an aluminum alloy can be used, for example. For the negative electrode internal terminal 17, from the viewpoint of improving the bonding strength with the negative electrode plate 41c (or the non-forming portion 41a of the negative electrode active material layer), copper or a copper alloy can be used, for example.

[0053] In this embodiment, the positive external terminal 14 and the negative external terminal 15 are mounted to the sealing plate 12 via a gasket 18. Additionally, the positive internal terminal 16 and the negative internal terminal 17 are mounted to the back (inner side) of the sealing plate 12 via an insulator 19. There are no particular limitations on the materials of the gasket 18 and the insulator 19. Insulating materials with excellent chemical resistance and weather resistance can be used for the gasket 18 and the insulator 19. For example, resins such as tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), polyethylene (PE), polypropylene (PP), and polyphenylene sulfide (PPS) can be used for the gasket 18 and the insulator 19.

[0054] Electrolyte

[0055] Regarding the non-aqueous electrolyte disclosed herein, carbonates are included to improve battery performance from the viewpoints of enhancing charge carrier conductivity and suppressing the long-term degradation of the non-aqueous electrolyte. Examples of carbonates include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC). It should be noted that these solvents can be used alone or in combination of two or more.

[0056] In non-aqueous electrolytes, film-forming agents, gas generators, dispersants, thickeners, anti-static agents, or supporting salts can be added, provided that the technical effects of this disclosure are not significantly impaired. Examples of film-forming agents include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), and oxalate complexes. Examples of oxalate complexes include lithium bis(oxalate)borate (Li[B(C2O4)2]; LiBOB) and lithium difluorooxalateborate (Li[BF2(C2O4)]; LBFO). Examples of gas generators and anti-static agents include biphenyl (BP) and cyclohexylbenzene (CHB). Examples of supporting salts include LiPF6, LiBF4, LiClO4, and LiFSI.

[0057] <Electrode>

[0058] The positive electrode 30 and negative electrode 40 of the lithium-ion secondary battery 1 according to this embodiment have active material layers with the configuration disclosed herein. Figure 5 An exploded view schematically showing the structure of the wound electrode body 20 is provided. The positive electrode 30 includes a positive electrode current collector foil 31 and a positive electrode active material layer 32. The negative electrode 40 includes a negative electrode current collector foil 41 and a negative electrode active material layer 42. Spacers 50a and 50b are interposed between the positive electrode 30 and the negative electrode 40.

[0059] In this embodiment, the electrode body is a wound electrode body 20 formed by winding a rectangular positive electrode 30 and a negative electrode 40 together with rectangular separators 50a and 50b. It should be noted that the electrode body is not limited to this; it can also be a stacked electrode body formed by alternately overlapping positive and negative electrodes with separators. Furthermore, there is no particular limitation on the number of wound electrode bodies 20 housed in the housing 10. Multiple electrode bodies can be housed in the housing 10 (e.g., multiple battery cells overlapped in the thickness direction).

[0060] <Negative electrode and negative electrode active material layer>

[0061] like Figure 5 As shown, the negative electrode 40 includes: a rectangular negative electrode current collector foil 41, and a negative electrode active material layer 42 formed on the surface of the negative electrode current collector foil 41. The negative electrode active material layer 42 contains a negative electrode active material capable of reversibly absorbing and releasing charge carriers (e.g., lithium ions), that is, capable of absorbing charge carriers during charging and releasing charge carriers during discharging. It should be noted that the negative electrode active material layer 42 can be formed on one or both sides (in this case, both sides) of the negative electrode current collector foil 41. Additionally, as... Figure 4 and Figure 5As shown, the negative electrode 40 may have a non-formed portion 41a of the negative active material layer 42, where the negative active material layer 42 is not formed and the negative current collector foil 41 is exposed. The non-formed portion 41a is provided at one end of the wound electrode body 20. In this embodiment, a plurality of negative electrode plates 41c are intermittently arranged at predetermined positions along the length direction of the negative electrode 40 in the non-formed portion 41a. Each of the plurality of negative electrode plates 41c protrudes in the width direction of the wound electrode body 20. While wound, the plurality of negative electrode plates 41c are positioned at positions determined by alignment. The internal terminal 17 of the negative electrode can be connected to the negative electrode plate 41c.

[0062] The negative electrode current collector foil 41 in this embodiment is rectangular, and its shape and size are not particularly limited, and can be appropriately determined according to the battery design. As for the material of the negative electrode current collector foil 41, known negative electrode current collector foils used in energy storage devices can be used, and there are no particular limitations. For example, the material of the negative electrode current collector foil 41 is copper or a copper alloy.

[0063] In the negative electrode active material layer 42 disclosed herein, at least graphite (graphite) particles 43 are included as the negative electrode active material. These graphite particles 43 have the following characteristics: A charge cycle of 30% to 80% and a discharge cycle of 80% to 30% is defined as one cycle. After at least one such charge-discharge cycle, the aforementioned square secondary battery is removed. In an electron microscope image of the osmium-stained negative electrode, at least 300 graphite particles are randomly selected. The number (A) of the stained graphite particles 44 within these particles divided by the total number of graphite particles (B) is less than 0.5. That is, Equation (1) A / B < 0.5. Furthermore, the orientation degree of the graphite particles 43 in the negative electrode active material layer 42 of this disclosure is 180° or less. The graphite particles 43 used in the battery pack of this disclosure will be described below.

[0064] The graphite particle 43, which has an A / B ratio of <0.5 as described above in formula (1), is a particle that does not or is unlikely to react with the electrolyte inside the particle. It should be noted that the term "particle interior" as used in this specification refers to the closed region inside formed by a single particle. There are almost no pores on the surface of the graphite particle 43 that connect to the particle interior, so non-aqueous electrolytes do not penetrate the particle interior. Figure 6 This image schematically illustrates a scanning electron microscope (SEM) photograph of the osmium-stained negative electrode active material layer 42. Figure 6The image shown illustrates the process of firstly, a charge cycle consisting of a charge rate of 30% to 80% and a discharge rate of 80% to 30% is defined as one cycle. After at least one such charge-discharge cycle, the negative electrode 40, opposite the positive electrode 30, is removed from the lithium-ion secondary battery 1. The removed negative electrode 40 is then stained with osmium tetroxide. It should be noted that, regarding the staining method, the negative electrode 40 can be immersed in an aqueous osmium tetroxide solution or exposed to the vapor of the aqueous osmium tetroxide solution. Osmium tetroxide precipitates due to its reaction with the double bonds (C=C) of the binder and by-reaction product 45 present in the negative electrode 40. It should be noted that the binder does not penetrate the particle interior through the pores described above. Therefore, the stained areas inside the particle can be considered as by-reaction product 45. That is, particles whose interiors are not stained with osmium can be determined to be free of electrolyte by-reaction product 45. Next, the osmium-stained negative electrode 40 is embedded in resin and then cut to create a cut surface. Then, using a scanning electron microscope (SEM), a reflected electron image is obtained from the cut surface, thus enabling the acquisition of... Figure 7 The photograph shown. Then, more than 300 graphite particles were randomly selected from the graphite particles observed in the reflected electron image. For each selected graphite particle, the number (A) of the graphite particles 44 that were stained inside the particle and the total number of selected graphite particles (B) were calculated, and A / B was calculated. When this value (A / B) is less than 0.5, the expansion of the graphite particles is suppressed. It should be noted that if the brightness of the osmium adsorbed part inside the graphite particle is higher than or equal to the brightness of the negative electrode current collector foil in the same image, the graphite particle is determined to be stained inside the particle. From the viewpoint of further suppressing the expansion of graphite particles, A / B is preferably less than 0.45, more preferably less than 0.4, and even more preferably less than 0.35.

[0065] The graphite particles 43 contained in the negative electrode active material layer 42 of this disclosure are specially treated graphite particles that can exert the technical effects of this disclosure, and can be appropriately selected from commercially available graphite particles. Preferably, the graphite particles 43 used do not have pores on their surface. If the surface of the graphite particles 43 does not have pores connecting to the interior of the particles, non-aqueous electrolytes will not penetrate into the interior of the particles. This suppresses the generation of electrolyte byproducts inside the particles. Those skilled in the art can predict whether the graphite particles used are suitable for the battery pack of this disclosure by confirming the presence or absence of pores on the particle surface using electron microscopy images. More preferably, those skilled in the art can appropriately select the appropriate particles by performing preliminary tests (such as the aforementioned osmium staining). For example, even if the surface of the prepared graphite particles has pores, by performing treatments such as coating the graphite particles with resin or the like and then firing them, or filling the pores connecting to the internal space, the pores can be eliminated, and graphite particles 43 suitable for exerting the technical effects of this disclosure can be produced.

[0066] The orientation degree of the graphite particles 43 contained in the negative electrode active material layer 42 disclosed herein is 180 or less. By aligning the graphite particles 43 in the direction perpendicular to the negative electrode current collector foil 41, the charge carriers can easily move in the thickness direction of the negative electrode active material layer 42 (the direction perpendicular to the negative electrode current collector foil 41). As a result, the diffusion resistance of the charge carriers is reduced, and thus the overvoltage of the negative electrode 40 during charging and discharging is suppressed. This effect can improve the cycle capacity retention rate of the secondary battery by suppressing the degradation of the negative electrode 40. The upper limit of the orientation degree is preferably 170 or less, more preferably 160 or less, and even more preferably 150 or less. Herein, "orientation degree" in this specification refers to the peak area I from the (110) facet of the graphite particles. (110) Peak area I from the (002) surface of graphite particles (002) The ratio (I) (002) / I (110) Orientation degree is an indicator of the degree of orientation of the hexagonal mesh of graphite particles relative to the thickness direction of the negative electrode (i.e., the normal direction of the negative electrode current collector foil 41 or the separators 50a, 50b). The smaller the orientation degree value, the more perpendicularly the orientation of the hexagonal mesh is aligned with the negative electrode current collector foil (or separators 50a, 50b). Conversely, the larger the orientation degree, the more parallelly aligned it is with the negative electrode current collector foil 41 (or separators 50a, 50b). It should be noted that the orientation degree can be calculated based on the results of X-ray crystal structure analysis. Typically, X-ray diffraction (XRD) using CuKα rays is used to determine the negative electrode active material layer taken from the energy storage device. In the XRD pattern, the peak from the (002) plane of the graphite particles appears approximately in the region of 2θ = 25.5° to 27.5°. Furthermore, the peaks from the (110) plane of the graphite particles appear approximately in the region of 2θ = 76.5° to 78.5°. Therefore, using commercially available analytical software, the peak areas I from the (002) plane of the graphite particles were calculated from the XRD pattern. (002) and the peak area I from the (110) surface (110) The peak area is used to calculate its ratio (I). (002) / I (110) This allows us to determine the degree of orientation.

[0067] Regarding the graphite particles 43, they can typically be easily oriented by applying a magnetic field to the negative electrode active material layer 42. As for the orientation method, conventionally known methods, such as those described in Japanese Patent Application Publication No. 2015-138644, can be employed. Before the paste-like negative electrode composite is coated onto the negative electrode current collector foil 41 and cured (completely dried), the orientation degree of the graphite particles 43 can be reduced by applying a magnetic field in the normal direction of the negative electrode current collector foil 41. It should be noted that for controlling the orientation of the graphite particles 43, it is preferable to arrange magnets in multiple interconnected configurations.

[0068] The average aspect ratio of the graphite particles 43 is not particularly limited as long as the technical effects of this disclosure are achieved. However, when the graphite particles 43 are perfectly spherical (i.e., aspect ratio 1.0), the orientation degree does not change, and therefore the technical effects of this disclosure tend to be smaller. Therefore, the lower limit of the average aspect ratio of the graphite particles 43 can be 1.1 or more. In addition, from the viewpoint of ensuring good passage (impregnation) of electrolyte in the thickness direction of the negative electrode active material layer 42, the lower limit of the average aspect ratio of the graphite particles 43 is preferably 1.2 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. If the average aspect ratio of the graphite particles 43 is too large, the compressibility and filling properties of the graphite particles 43 tend to deteriorate. Therefore, the upper limit of the average aspect ratio of the graphite particles 43 is preferably 20.0 or less, more preferably 15.0 or less, and even more preferably 10.0 or less. It should be noted that the average aspect ratio of the graphite particles 43 can be calculated, for example, by observing a SEM image of the cross-section of the negative electrode active material layer 42 taken from the secondary battery. First, obtain a planar SEM image of the graphite particles and define a rectangle circumscribed around the graphite particles. Calculate the aspect ratio by the ratio of the length of the longest side (the longest diameter along the long side direction) to the length of the shortest side (the diameter orthogonal to the long side direction). For the average aspect ratio, calculate the arithmetic mean of the aspect ratios of multiple graphite particles randomly selected from the SEM image (e.g., more than 300 particles).

[0069] Furthermore, for the negative electrode active material layer 42 containing graphite particles 43 with an average aspect ratio exceeding 1.0, it is preferable that the orientation degree of the graphite particles 43 increases when compressed until the thickness of the negative electrode active material layer 42 reaches 90%. By applying pressure to the negative electrode active material layer 42, the graphite particles 43, which are oriented perpendicularly to the negative electrode current collector foil 41 (i.e., the graphite particles 43 are approximately orthogonal to the negative electrode current collector foil 41), are laid horizontally. At this time, with the orientation degree of the graphite particles 43 increasing (typically by more than 10), it is assumed that the long side direction of the graphite particles 43 corresponds to the planar direction (lattice plane: 002 plane) of the graphite layer. Therefore, such a negative electrode active material layer 42 can further improve the technical effect of this disclosure.

[0070] The graphite particles 43 can be natural graphite or artificial graphite. Alternatively, the graphite particles 43 can be amorphous carbon-coated graphite, where graphite is coated with an amorphous carbon material. In the negative electrode active material layer 42, the aforementioned graphite particles 43 can be used in combination with the negative electrode active material used in the negative electrode of a typical lithium-ion secondary battery. Examples of negative electrode active materials other than graphite particles 43 include carbon materials such as soft carbon (easily graphitized carbon), hard carbon (difficult-to-graphitize carbon), and carbon nanotubes; metal oxide materials such as silicon oxide, titanium oxide, vanadium oxide, and lithium-titanium composite oxides; metal nitride materials such as lithium nitride and lithium-cobalt composite nitrides; and silicon compounds.

[0071] The average particle size of the graphite particles 43 is not particularly limited as long as it does not significantly impair the technical effects of this disclosure. The average particle size of the graphite particles 43 is typically 30 μm or less. If the average particle size is small, the electrode density increases; therefore, from the viewpoint of increasing the capacity of the lithium-ion secondary battery 1, the upper limit of the average particle size of the graphite particles 43 is preferably 25 μm or less, more preferably 20 μm or less. It should be noted that the average particle size of the active material (here, graphite particles 43) can be determined using the 50% volume percentage particle size (D50 particle size) based on laser diffraction-light scattering.

[0072] Regarding the content of graphite particles 43 in the negative electrode active material layer 42, when the total weight of the solid components of the negative electrode active material layer 42 is set to 100 wt%, it can be 90 wt% or more, preferably 95 wt% or more, and more preferably 97 wt% or more.

[0073] The negative electrode active material layer 42 may contain various additives such as binders, conductive additives, inorganic fillers, or thickeners, provided that it does not significantly impair the technical effects disclosed herein. For the negative electrode active material layer 42, for example, a binder (or, as needed, conductive additives, inorganic fillers, etc.) may be added to the negative electrode active material and dispersed in a suitable solvent (ion-exchanged water, organic solvents, etc.) to prepare a paste-like composition. By coating an appropriate amount of this composition onto the surface of the negative electrode current collector foil 41 and drying it, the negative electrode active material layer 42 can be formed. It should be noted that these various additives may be used alone or in combination of two or more.

[0074] Examples of adhesives added to the negative electrode active material layer 42 include adhesives used in non-aqueous pastes and adhesives used in water-soluble pastes. For example, adhesives used in non-aqueous pastes include halogenated vinyl resins such as polyvinylidene fluoride (PVDF) and polyvinylidene chloride (PVDC), and polyoxyethylene resins such as polyethylene oxide (PEO). In the case of using an aqueous paste, water-soluble or water-dispersible polymer materials are preferred. For example, adhesives used in aqueous pastes include polytetrafluoroethylene (PTFE) and styrene-butadiene rubber (SBR). Among these, adhesives used for the negative electrode active material layer are preferably low-cost and have low environmental impact, so SBR, for example, can be used. By adding an adhesive to the negative electrode active material layer 42, the adhesion (bonding strength) between the negative electrode active material layer and the negative electrode current collector foil or separator can be improved. Furthermore, the occurrence of cracking of the negative electrode active material layer during the manufacturing process of the energy storage device can be reduced.

[0075] When a binder is included in the negative electrode active material layer 42, there is no particular limitation on the binder content. The lower limit of the binder content can be 0.5 wt% or more, preferably 0.8 wt% or more, more preferably 1.0 wt% or more, and even more preferably 1.5 wt% or more. Furthermore, by including a large amount of binder in the negative electrode active material, the resistance value of the lithium-ion secondary battery 1 increases. Therefore, from the viewpoint of improving cycle characteristics, the upper limit of the binder content is preferably 5.0 wt% or less, more preferably 4.0 wt% or less, and even more preferably 3.0 wt% or less.

[0076] Examples of conductive additives contained in the negative electrode active material layer 42 include acetylene black, needle graphite, CNTs, and metal powders. Examples of inorganic fillers include aluminum hydroxide, silicon dioxide, alumina, zirconium oxide, titanium dioxide, boehmite, or magnesium oxide. Examples of thickeners include carboxymethyl cellulose (CMC) and methyl cellulose (MC).

[0077] The thickness (film thickness) of the negative electrode active material layer 42 is not particularly limited as long as it does not significantly impair the technical effects of this disclosure. Regarding the lower limit of the film thickness of the negative electrode active material layer 42, from the viewpoint of improving the capacity density of the energy storage device, 30 μm or more is preferred, 50 μm or more is more preferred, and 60 μm or more is even more preferred. Furthermore, the upper limit of the film thickness may be 150 μm or less, 125 μm or less, or 100 μm or less. It should be noted that the above-mentioned film thickness of the negative electrode active material layer 42 refers to the average thickness of the negative electrode active material layer 42 coated on each single side of the negative electrode current collector foil 41.

[0078] The true density of the negative electrode active material layer 42 is not particularly limited as long as it does not significantly impair the technical effects of this disclosure. The true density of the negative electrode active material layer 42 can be adjusted using the pressure treatment conditions applied to the negative electrode active material layer 42 during the fabrication of the negative electrode 40. If the true density of the negative electrode active material layer increases, the secondary battery and the battery pack having the secondary battery tend to have higher capacity. Therefore, the lower limit of the true density of the negative electrode active material layer 42 is preferably 0.8 g / cm³. 3 More preferably 1.0 g / cm 3 The above is further optimized to 1.3 g / cm³. 3 That's all. Additionally, the upper limit of the true density of the negative electrode active material layer 42 can be 1.7 g / cm³. 3 The following value can be 1.6 g / cm³. 3 The following can be 1.5g / cm 3 the following.

[0079] <Positive electrode and positive electrode active material layer>

[0080] like Figure 5 As shown, the positive electrode 30 includes a rectangular positive electrode current collector foil 31 and a positive electrode active material layer 32 formed on the surface of the positive electrode current collector foil 31. The positive electrode active material layer 32 contains a positive electrode active material capable of reversibly absorbing and releasing charge carriers (e.g., lithium ions), that is, capable of releasing charge carriers during charging and absorbing charge carriers during discharging. It should be noted that the positive electrode active material layer 32 can be formed on one side or both sides (in this case, both sides) of the positive electrode current collector foil 31. The positive electrode 30 may have a non-formed portion 31a of the positive electrode active material layer where the positive electrode current collector foil 31 is exposed without the formation of the positive electrode active material layer 32. In this embodiment, as... Figure 5 As shown, the non-formed portion 31a of the positive electrode active material layer is provided at one end of the wound electrode body 20. In the non-formed portion 31a, a plurality of positive electrode plates 31c are intermittently arranged at predetermined positions along the length direction of the positive electrode 30. Each of the plurality of positive electrode plates 31c protrudes in the width direction of the wound electrode body 20. In the wound state, the plurality of positive electrode plates 31c are positioned at positions determined by alignment. The internal terminal 16 of the positive electrode can be connected to the positive electrode plate 31c. Furthermore, in this embodiment, a positive electrode protective layer 31b is provided on the edge of the positive electrode active material layer 32 on the positive electrode current collector foil 31 (more specifically, the non-formed portion 31a of the positive electrode active material layer). The positive electrode protective layer 31b is a layer that protects the non-formed portion 31a of the positive electrode active material layer and may be a layer containing inorganic fillers.

[0081] Regarding the material of the positive electrode current collector foil 31, any known positive electrode current collector foil 31 used in batteries can be used, without particular limitation. For example, the material of the positive electrode current collector foil 31 can be aluminum or an aluminum alloy. As the positive electrode active material layer 32, the positive electrode active material can be any positive electrode active material used in the positive electrode of a typical lithium-ion secondary battery. Specifically, the positive electrode active material is a lithium composite metal oxide with a layered rock salt structure, spinel structure, or olivine structure, etc. Examples of lithium composite metal oxides include LiCoO2, LiNiO2, LiFeO2, and LiNiO2. x Co y Mn 1-x -yO2(NCM), LiNi 0.5 Mn 1.5 O4, LiNi 0.8 Co 0.15 Al 0.05 O2 (NCA), LiCrMO4, LiMn2O4, LiFePO4 (LFP), etc. It should be noted that these positive electrode active materials can be used individually or in combination of two or more. From the viewpoint of improving the cycle characteristics of the battery, NCM is preferred as the positive electrode active material. It should be noted that the positive electrode active material layer 32 may contain various additives such as binders, conductive additives, inorganic fillers, or thickeners.

[0082] <Separator>

[0083] The separators 50a and 50b involved in this embodiment are porous sheets with insulating properties. However, the shape and size of the separators 50a and 50b are not particularly limited and can be appropriately determined according to the battery design. Typically, the separators 50a and 50b insulate the positive electrode 30 and the negative electrode 40, therefore the size of the separators 50a and 50b is larger than that of the positive electrode 30 and the negative electrode 40. As for the material of the separators 50a and 50b, known separators used in batteries can be used, and there are no particular limitations. For example, as the material of the separators 50a and 50b, polyolefins such as polyethylene or polypropylene, polyesters, cellulose, or resins such as polyamides are preferred. In addition, a heat-resistant layer can be provided on the surface of the separators 50a and 50b, as long as it does not significantly impair the technical effects disclosed herein.

[0084] like Figure 5 As shown, the width Ln of the negative electrode active material layer 42 is, for example, wider than the width Lp of the positive electrode active material layer 32. The width Ls of the separators 50a and 50b is wider than that of the negative electrode active material layer 42. That is, as... Figure 5As shown, Lp < Ln < Ls. The positive electrode 30, the first separator 50a, the negative electrode 40, and the second separator 50b are aligned with their respective length directions, and are sequentially overlapped and wound. The negative electrode active material layer 42 covers the positive electrode active material layer 32 while being separated by separators 50a and 50b. The negative electrode active material layer 42 is covered by separators 50a and 50b. The positive electrode plate 31c of the positive electrode current collector foil 31 and the negative electrode plate 41b of the negative electrode current collector foil 41 are arranged such that they extend from separators 50a and 50b towards opposite sides in the width direction. The edges of the positive electrode protective layer 31b and the side of the negative electrode 40 where the negative electrode plate 41c is located are opposite each other via separators 50a and 50b. It should be noted that... Figure 4 As shown, the wound electrode body 20 is arranged in such a way that it can be accommodated in the housing 10, along the winding axis WL (see reference). Figure 5 The flat surface 21 of the winding electrode 20 is flattened. The winding electrode 20 is housed such that the flat surface 21 abuts against the inner side of the long side surface 11b1 or long side surface 11b2 of the housing 10. The positive electrode 31c protrudes from one side of the lamination surface 22. In addition, the negative electrode 41c protrudes from the other side of the lamination surface 22. Along the winding axis WL, the positive electrode 31c is arranged on one side and the negative electrode 41c is arranged on the opposite side.

[0085] <Effects of this implementation method>

[0086] According to the battery pack 100 described above, for the negative electrode that has undergone orientation treatment, the expansion in the horizontal direction of the negative electrode current collector foil can also be suppressed, thus suppressing the bending of the negative electrode.

[0087] first, Figure 7 This diagram schematically illustrates the situation where side reactions easily occur inside graphite particles in a scanning electron microscope image obtained from an osmium-stained negative electrode active material layer. In the conventional negative electrode 40a shown here, the graphite particles 44 that are prone to side reactions inside the particles and the negative electrode 40a containing a large amount of these graphite particles 44 (typically, A / B ≥ 0.5) are explained. Figure 7 As shown, by-reaction products 45, accumulated inside graphite particles 44, react with osmium and become stained. In the negative electrode 40a, by-reaction products are generated due to the decomposition of non-aqueous electrolytes during charging and discharging. For example... Figure 7As shown, by-products 45 of the non-aqueous electrolyte accumulate in the voids of the graphite particles 44 (more specifically, the inner surface or internal space of the graphite particles 44). These graphite particles 44 expand significantly due to repeated charging and discharging. Multiple pores connected to these voids exist on the surface of the graphite particles 44, allowing components of the non-aqueous electrolyte (such as charge carriers) to penetrate the interior of the graphite particles 44 during charging and discharging. Therefore, it is believed that the accumulation of by-products 45 occurs within the graphite particles 44. Figure 8 This is an illustrative diagram illustrating the expansion of graphite particles 44 to demonstrate orientation. Figure 8 In this configuration, the orientation of the graphite layer 46 (i.e., the connection of the planar six-membered rings of carbon) is opposite to the long side orientation of the graphite particles 44. When the graphite particles 44 are oriented vertically relative to the negative electrode current collector foil 41, they expand horizontally relative to the negative electrode current collector foil 41. Consequently, the negative electrode 40a may expand horizontally in the current collector foil, resulting in bending. Figure 9 This is an explanatory diagram illustrating the bent state of the negative electrode 40a. In the bent state, a gap is created between the negative electrode 40a and the separator 50a, or between the positive electrode 30 and the separator 50a, thus reducing the cycle capacity retention.

[0088] The battery pack 100 disclosed here is as follows Figure 1 and Figure 2As shown, the battery comprises multiple square secondary batteries (here, lithium-ion secondary batteries 1). The multiple lithium-ion secondary batteries 1 are stacked using spacers 120. The spacers 120 include an elastic layer. In this embodiment, the spacers are entirely composed of an elastic layer. If the elastic modulus of the spacers 120 is too low, the negative electrode 40 may bend. However, if the elastic modulus of the spacers 120 is too high, the wound electrode body 20 will be excessively compressed, thus reducing the cycle capacity retention rate. Therefore, the elastic modulus of the elastic layer of the spacers 120 is 0.3 MPa or more and 5 MPa or less. Furthermore, the lithium-ion secondary battery 1 has an electrode body (here, a wound electrode body 20), which includes: a negative electrode 40 having a negative electrode current collector foil 41 and a negative electrode graphite layer 42 containing graphite particles 43 formed on the negative electrode current collector foil 41, and a positive electrode 30. Additionally, the lithium-ion secondary battery 1 also has an electrolyte containing carbonate and a square casing 10 housing the electrode body. Here, the orientation degree of the graphite particles 43 contained in the negative electrode active material layer 42 is 180 or less. By reducing the orientation degree, the cycle capacity retention rate is improved. However, the graphite particles 43 become prone to expansion in the horizontal direction of the negative electrode current collector foil 41, so the negative electrode 40 may bend. For the graphite particles 43, more than 300 graphite particles 43 are randomly selected from the electron microscope image of the osmium-stained negative electrode 40 after charging, such that the number (A) of the stained graphite particles 44 inside these particles divided by the total number of graphite particles (B) is less than 0.5. Therefore, the expansion of graphite particles 43 can be suppressed, the bending of the negative electrode 40 can be suppressed, and the cycle capacity retention rate can be improved.

[0089] The preferred embodiments of this disclosure have been described above based on the accompanying drawings, but such description is not limiting and various changes are certainly possible.

[0090] Example

[0091] The following examples and comparative examples illustrate the battery pack of this disclosure in detail. It should be noted that this disclosure is not intended to be limited to the content shown in these examples.

[0092] <Example 1: Fabrication of the Positive Electrode>

[0093] A paste for forming the positive electrode active material layer was prepared by mixing 98 wt% NCM powder as the positive electrode active material, 1 wt% PVDF as the binder, and 1 wt% acetylene black as the conductive additive, and further adding a solvent. It should be noted that N-methyl-2-pyrrolidone (NMP) was used as the solvent. Next, an aluminum foil with a thickness of 13 μm was prepared. The above-mentioned paste for forming the positive electrode active material layer was coated on both sides of the aluminum foil. At this time, adjustments were made to the coating so that the combined thickness of the aluminum foil and the positive electrode active material layers on both sides (i.e., the average film thickness of the positive electrode) was 140 μm. A notched wheel coater (registered trademark) was used for coating. After coating the positive electrode active material layer, it was allowed to dry naturally, and then heated and dried at 120°C. Then, leaving the conductive portion, it was cut to a length of 5 cm × width of 5 cm to produce a positive electrode sheet.

[0094] <Example 1: Fabrication of the negative electrode>

[0095] First, graphite particles for use in the negative electrode are prepared. As graphite particles for use in the negative electrode, particles designed to suppress the accumulation of by-reaction products inside the particles and particles not designed in this way are mixed in any proportion.

[0096] Next, 98 wt% of the graphite particles prepared above as the negative electrode active material, 1 wt% of SBR as the binder, and 1 wt% of CMC as the thickener are mixed, and then a solvent is added to prepare a paste for forming the negative electrode active material layer. It should be noted that deionized water is used as the solvent. Next, a copper foil with a thickness of 8 μm is prepared. The above-mentioned paste for forming the negative electrode active material layer is applied to both sides of the copper foil. At this time, adjustments are made to ensure that the combined thickness of the copper foil and the negative electrode active material layers on both sides (i.e., the average film thickness of the negative electrode) is 160 μm. Before the applied paste for forming the negative electrode active material layer cures, a magnetic field is applied with the magnetic field lines pointing towards the normal direction of the copper foil. The conditions for application are set as a maximum magnetic flux density of 350 mT and an application time of 5 seconds. Then, after natural drying, it is heated and dried at 120°C. The conductive portion remains, and it is cut to a length of 5.4 cm × 5.4 cm to produce a negative electrode sheet.

[0097] <Fabrication of Laminated Bipolar Battery Cells>

[0098] As a separator, a porous polyolefin sheet of polyethylene with a length of 6cm, a width of 6cm, and a thickness of 16μm is prepared. The positive electrode sheet, separator, and negative electrode sheet are stacked sequentially and bonded together by compression. Then, an aluminum / PP laminated film is used to seal the bag with each conductive part exposed, creating a laminated bipolar battery cell with a length of 7cm, a width of 7cm, and a thickness of 2.5mm. It should be noted that the non-aqueous electrolyte is a solution prepared by dissolving LiBOB, a boron-containing coating forming agent, at a concentration of approximately 0.5wt% in an organic mixed solvent (EC:EMC:DMC = 1:1:1). Next, the laminated bipolar battery cell prepared above is charged to 3.7V at a constant current of 0.1C and subjected to a heat treatment at 60°C for 10 hours. Then, a charge-discharge cycle is performed at a constant current of 0.1C between 4.2V and 3.0V to complete the battery cell.

[0099] <Determination of the elastic modulus of spacers>

[0100] The elastic modulus of the spacer used in the test was determined beforehand. A silicone rubber spacer measuring 5 cm in length and 5 cm in width was prepared. Using a compression testing apparatus, the spacer was compressed at a compression rate of 30 N / min (12 kPa / min) until the compressive load per unit area of ​​the spacer reached 3.9 MPa. The compression load and the thickness after compression were measured. An FS curve was plotted from the obtained compression load and thickness after compression, and the elastic modulus in the range of 1% to 20% of the compression ratio was calculated.

[0101] <Determination of Orientation Degree of Graphite Particles>

[0102] Next, the completed laminated bipolar battery cell is disassembled. The negative electrode is removed while the electrolyte is being recovered. The orientation of the negative electrode active material layer on the removed negative electrode is determined using X-ray diffraction (XRD). Specifically, the negative electrode is irradiated with X-rays, and the peak area ratio of the (110) plane to the (002) plane is calculated. For XRD conditions, CuKα rays are used as the X-ray source, and measurements are taken in steps of 0.02° within the measurement range of 2θ = 20° to 100°.

[0103] <Determination of the ratio of graphite particles that produce reaction products internally>

[0104] The completed laminated bipolar battery cell was disassembled, and the electrolyte was recovered while the negative electrode was removed. 4% osmium tetroxide was heated to 50°C, and the negative electrode was exposed to the generated vapor for 1 hour to perform osmium tetroxide vapor staining. This caused osmium to adsorb onto the reaction products accumulated inside the graphite particles of the negative electrode. The negative electrode was then resin-embedded, exposing its cross-section. Reflected electron microscopy (SEM) was used to obtain a reflection electron image of the cut surface (acceleration conditions 10 kV). More than 300 graphite particles were randomly selected from the observed graphite particles. For each selected graphite particle, the number of stained graphite particles inside was calculated and divided by the total number of selected graphite particles.

[0105] <Evaluation of the battery pack construction>

[0106] The spacer is brought into contact with one side of the laminated bipolar battery cell. The thickness of the spacer before constraint is 0.35 times the thickness of the laminated bipolar battery cell when the thickness is set to 1 (in other words, 35% of the thickness of the laminated bipolar battery cell). Then, the laminated bipolar battery cell and the spacer are clamped together with a pair of stainless steel plates (the thickness of the stainless steel plates is 200% of the thickness of the laminated bipolar battery cell), constraining the spacer to 80% of its original thickness before constraint, thus creating an evaluation battery pack.

[0107] <Determination of Circulatory Capacity Maintenance>

[0108] The aforementioned evaluation battery pack was fixed to a load sensor. While monitoring the load at the center of the evaluation battery pack with the distance between a pair of stainless steel plates remaining constant, the battery was charged and discharged at 40°C with a constant current of 1C between 15% and 95% of its state of charge (SOC). The discharge capacity obtained at this point was defined as the initial discharge capacity. Next, 1000 charge-discharge cycles were performed at 40°C with a constant current of 0.25C between 15% and 95% of SOC. The discharge capacity obtained on the 1000th cycle was defined as the post-cycle discharge capacity. The cycle capacity retention rate (%) was calculated by dividing the post-cycle discharge capacity by the initial discharge capacity and expressing it as a percentage.

[0109] <Confirmation of the presence or absence of curvature>

[0110] The battery pack was disassembled for evaluation after the cycle capacity retention rate was measured. The negative electrode was removed and the presence or absence of bending (electrode deflection) was visually confirmed.

[0111] <Reaction Ratio>

[0112] In the determination of cyclic capacity retention, the load at 95% SOC on the 1000th cycle was measured.

[0113] <Examples 2-5, Comparative Examples 1-8>

[0114] As shown in Table 1, the results were the same as in Example 1, except that the spacers, the orientation of the graphite particles, and the ease with which by-reaction products were generated within the graphite particles were changed. In Comparative Examples 7 and 8, the tests were conducted without spacers. In this case, the constraint of the metal plate was equivalent to a spacer with an elastic modulus of 12 MPa. The orientation was adjusted by shortening the application time. The proportion of particles that generated reaction products within the graphite particles was adjusted by changing the mixing ratio of the prepared graphite particles. It should be noted that the reaction ratio is expressed as a ratio relative to Comparative Example 8 (the value obtained by dividing the value measured in each test example by the value measured in Comparative Example 8).

[0115] Table 1

[0116]

[0117] Based on the above test results, compared to Comparative Example 7 without spacers, Examples 1 and 2 with spacers showed improved cycle capacity retention. Furthermore, compared to Comparative Example 1 with high orientation, Example 1 with low orientation showed improved cycle capacity retention. However, no improvement in cycle capacity retention was observed in Comparative Example 7 with low orientation and Comparative Example 8 with high orientation, indicating that the cycle capacity retention does not improve when there are no spacers. Compared to Comparative Examples 2-5 with a higher proportion of particles generating reaction products internally, Examples 1-5 with a lower proportion of particles generating reaction products internally showed improved cycle capacity retention. However, no improvement in cycle capacity retention was observed in Comparative Example 2 with a higher proportion of particles generating reaction products internally and Comparative Example 1 with a lower proportion of particles generating reaction products internally, indicating that the cycle capacity retention does not improve when the orientation is high. In Comparative Example 6 with low elastic modulus of the spacer, bending of the negative electrode was observed, resulting in a decrease in cycle capacity retention. Furthermore, even when the elastic modulus of the spacer was within the preferred range and the orientation of the graphite particles was low, in Comparative Examples 3-5, where the proportion of particles generating reaction products internally was high, bending of the negative electrode and a decrease in cycle capacity retention were observed. In Examples 1-5, however, by reducing the proportion of particles generating reaction products internally, the cycle capacity retention was improved.

[0118] The above examples of the technology disclosed herein are illustrated in detail, but these are merely illustrative and do not limit the scope of the patent claims. The technology described in the patent claims includes technical solutions that involve various modifications and alterations to the specific examples illustrated above.

[0119] The techniques disclosed herein may be appropriately omitted or combined in accordance with the law, provided that no particular problems arise. Furthermore, this specification includes the disclosures described in the following items.

[0120] Item 1: A battery pack comprising a plurality of square secondary batteries, wherein the plurality of square secondary batteries are stacked by spacers, the spacers comprising an elastic layer having an elastic modulus of 0.3 MPa or more and 5 MPa or less, the square secondary batteries comprising: an electrode body comprising a negative electrode and a positive electrode having a negative electrode current collector foil and a negative electrode active material layer comprising graphite particles formed on the negative electrode current collector foil; a non-aqueous electrolyte comprising carbonate; and a housing containing the electrode body and the non-aqueous electrolyte, wherein the... The graphite particles contained in the negative electrode active material layer have an orientation degree of 180 or less. A charge cycle is defined as a charge rate of 30% to 80% or more and a discharge rate of 80% to 30% or more. After the square secondary battery has undergone at least one charge-discharge cycle, more than 300 graphite particles are randomly selected from the electron microscope image of the osmium-stained negative electrode. The value obtained by dividing the number of stained graphite particles (A) inside these particles by the total number of graphite particles (B) is less than 0.5.

[0121] Item 2: The battery pack according to Item 1, wherein the average aspect ratio of the graphite particles is 1.2 or higher.

[0122] Explanation of reference numerals in the attached figures

[0123] 1. Lithium-ion secondary battery

[0124] 10. Shell

[0125] 11 Main Body

[0126] 11a Bottom wall

[0127] 11b1, 11b2 Long side

[0128] 11c1, 11c2 Short side

[0129] 12 Sealing Board

[0130] 13 Safety valve

[0131] 14 Positive external terminal

[0132] 15 Negative external terminal

[0133] 16 Positive internal terminals

[0134] 17 Negative internal terminal

[0135] 18 gaskets

[0136] 19 Insulators

[0137] 20. Winded electrode body

[0138] 21 Plane

[0139] 22-layer facets

[0140] 30 Positive electrode

[0141] 31 Positive electrode current collector foil

[0142] 31a Non-forming portion of the positive electrode active material layer

[0143] 31b Positive electrode protective layer

[0144] 31C Positive Electrode

[0145] 32 Positive electrode active material layer

[0146] 40 Negative electrode

[0147] 40a negative electrode

[0148] 41 Negative electrode current collector foil

[0149] 41a Non-forming portion of the negative electrode active material layer

[0150] 41c negative electrode plate

[0151] 42 Negative electrode active material layer

[0152] 43 Graphite particles

[0153] 44 Graphite particles

[0154] 45 By-products

[0155] 46 graphite layers

[0156] 50a, 50b separators

[0157] 100 battery pack

[0158] 110 Constraint Members

[0159] 111 base plate

[0160] 112a and 112b end plates

[0161] Side panels 113a and 113b

[0162] 113c Rib

[0163] 114 screws

[0164] 120 spacers

Claims

1. A battery pack comprising a plurality of square secondary batteries arranged in a predetermined direction, and spacers respectively disposed between said arranged square secondary batteries. The spacer comprises an elastic layer with an elastic modulus of 0.3 MPa or more and 5 MPa or less. The square secondary battery includes: An electrode body comprising a negative electrode having a negative current-collecting foil and a negative active material layer formed on the negative current-collecting foil, and a positive electrode having a positive current-collecting foil and a positive active material layer formed on the positive current-collecting foil; Non-aqueous electrolytes containing carbonates; and A housing that contains the electrode body and the non-aqueous electrolyte. The negative electrode active material layer contains graphite particles as the negative electrode active material. The orientation degree of the graphite particles is less than 180. A charge cycle is defined as a charge rate of less than 30% to more than 80% and a discharge rate of more than 80% to less than 30%. After at least one charge-discharge cycle, the square secondary battery is removed, and more than 300 graphite particles are randomly selected from the electron microscope image of the osmium-stained negative electrode. The value obtained by dividing the number A of stained graphite particles inside these particles by the total number B of graphite particles is less than 0.

5.

2. The battery pack according to claim 1, wherein, The graphite particles have an average aspect ratio of 1.2 or higher.

Citation Information

Patent Citations

  • Manufacturing method for graphite containing composition, manufacturing method for negative electrode for lithium secondary battery, and manufacturing method for lithium secondary battery

    JP2003197189A

  • Nonaqueous electrolyte secondary battery

    JP2015138644A

  • Carbon material for nonaqueous secondary battery negative electrode and nonaqueous secondary battery

    JP2016184534A

  • Battery pack

    JP2018181765A